Cystic fibrosis transmembrane conductance regulator mutations at a referral center for cystic fibrosis - Coutinho, Cyntia Arivabeni de Araújo Correia (Sociedade Brasileira de Pneumologia e Tisiologia Paulo, 2013)

(untitled)
OBJECTIVE: To determine the frequency of six mutations (F508del, G542X, G551D, R553X, R1162X, and N1303K) in patients with cystic fibrosis (CF) diagnosed, at a referral center, on the basis of abnormal results in two determinations of sweat sodium and chloride concentrations. METHODS: This was a cross-sectional study involving 70 patients with CF. The mean age of the patients was 12.38 ± 9.00 years, 51.43% were female, and 94.29% were White. Mutation screening was performed with polymerase chain reaction (for F508del), followed by enzymatic digestion (for other mutations). Clinical analysis was performed on the basis of gender, age, ethnicity, pulmonary/gastrointestinal symptoms, and Shwachman-Kulczycki (SK) score. RESULTS: All of the patients showed pulmonary symptoms, and 8 had no gastrointestinal symptoms. On the basis of the SK scores, CF was determined to be mild, moderate, and severe in 22 (42.3%), 17 (32.7%), and 13 (25.0%) of the patients, respectively. There was no association between F508del mutation and disease severity by SK score. Of the 140 alleles analyzed, F508del mutation was identified in 70 (50%). Other mutations (G542X, G551D, R553X, R1162X, and N1303K) were identified in 12 (7.93%) of the alleles studied. In F508del homozygous patients with severe disease, the OR was 0.124 (95% CI: 0.005-0.826). CONCLUSIONS: In 50% of the alleles studied, the molecular diagnosis of CF was confirmed by identifying a single mutation (F508del). If we consider the analysis of the six most common mutations in the Brazilian population (including F508del), the molecular diagnosis was confirmed in 58.57% of the alleles studied.